METHODS OF APPLYING VARIATIVE PROGRAMS TO ASSESS THE PHYSICAL PREPAREDNESS OF PRESCHOOLERS (Proximus Journal of Sports Science and Physical Education, 2025)
The article examines the importance of variative (optional) programs in preschool educational institutions, as well as the criteria of play-based (movement-based) tests used in monitoring the physical preparedness of children and the indicators applied in their implementation.